FRI0590 BIOMARKERS OF HEMODYNAMIC SEVERITY OF SYSTEMIC-SCLEROSIS ASSOCIATED PULMONARY ARTERIAL HYPERTENSION BY SERUM PROTEOME ANALYSIS. (2nd June 2020) - Sanges, S.; Rice, L.; Tu, L.; Cracowski, J. L.; Montani, D.; Mantero, J.; Ternynck, C.; Marot, G.; Hachlla, E.; Launay, D.; Humbert, M.; Guignabert, C.; et al.
Abstract : Objectives: To investigate alterations in the serum proteome of patients with systemic sclerosis (SSc)-associated pulmonary hypertension (PAH), to identify proteins that correlated with hemodynamic severity and to determine their possible pathogenic role. Methods: Patients were included if they fulfilled the following criteria: diagnosis of limited cutaneous SSc, no extensive interstitial lung disease (ILD), and no treatment with PAH-specific therapy. Patients were classified as cases if they had a definitive diagnosis of PAH confirmed by right heart catheterization (RHC) and a serum sample collected on the same day as RHC. They were classified as controls if they had no sign suggestive of PAH on echocardiography. Results: In a first exploratory step, serum expression of 1129 proteins was assessed in 15 cases and 16 controls by a high-throughput proteomic assay (SOMAscan). We identified 53 proteins differentially expressed between the 2 groups. Among these 53 candidates, only 2 correlated significantly with pulmonary vascular resistance (PVR): chemerin ( p= 0.01, ρ= 0.62) and SET nuclear proto-oncogen (SET) ( p= 0.01, ρ= 0.62). To validate these results, serum levels of chemerin and SET were measured by ELISA assay in 25 additional cases and 19 additional controls. Chemerin levels were confirmed to be significantly higher in cases ( p= 0.01) and correlated with PVR ( p= 0.01, ρ= 0.46). In a second step, to study the potential pathophysiological role of chemerin, we performed confocal immunofluorescence analyses on explanted lungs of healthy controls, SSc-ILD without PAH and SSc-PAH patients. Chemerin receptor, CMKLR1, was significantly increased on SSc-ILD and SSc-PAH pulmonary artery smooth muscle cells (PA-SMC). We then tested the effect of chemerin on PA-SMC proliferation by stimulating PA-SMCs from idiopathic pulmonary arterial hypertension (iPAH) patients with serum from SSc patients with and without PH, in the presence or absence of a CMKLR1 inhibitor. PA-SMCs from iPAH were confirmed to have higher mRNA expression of CMKLR1 than controls ( p= 0.03). Serum from SSc-PH patients induced a significantly higher PA-SMC proliferation ( p= 0.005) than serum from controls. This difference was no longer significant ( p= 0.69) when adding the CMKLR1 inhibitor α–NETA. Conclusion: Chemerin is a surrogate biomarker for PVR in SSc-PAH. Increased chemerin and its receptor, CMKLR1, contribute to the SSc-PAH pathogenesis by inducing PA-SMC proliferation. Acknowledgments: None Disclosure of Interests: Sebastien SANGES: None declared, Lisa Rice: None declared, Ly Tu: None declared, Jean-Luc Cracowski Grant/research support from: JL Cracowski received grants from United Therapeutic, Bioprojet and Topadur, David Montani Grant/research support from: Dr. MONTANI reports grants and personal fees from Actelion, grants and personal fees from Bayer, personal fees from GSK, personal fees from Pfizer, personal fees from MSD, personal fees from Chiesi, outside the submitted work, Julio Mantero: None declared, Camille Ternynck: None declared, Guillemette Marot: None declared, Eric Hachlla: None declared, David Launay Grant/research support from: Dr. Launay reports personal fees from Actelion, grants and personal fees from Takeda, grants and personal fees from CSL Behring, outside the submitted work., Marc Humbert Grant/research support from: Dr. Humbert reports personal fees from Actelion, grants and personal fees from Bayer, grants and personal fees from GSK, personal fees from Merck, from United Therapeutics, personal fees from Acceleron, outside the submitted work., Christophe Guignabert: None declared, Robert Lafyatis Grant/research support from: RL holds research grants from Formation, Elpidera and Kiniksa., Consultant of: R.L. has served as a consultant for Bristol Myers Squibb, Boehringer-Mannheim, Merck, Magenta and Genentech/Roche,